3 Tesla 1H MR spectroscopy of hip bone marrow in a healthy population, assessment of normal fat content values and influence of age and sex. Issue 2 (15th May 2013) - Pansini, Vittorio; Monnet, Aurélien; Salleron, Julia; Hardouin, Pierre; Cortet, Bernard; Cotten, Anne
<x xml:space="preserve">Abstract</x> Purpose To evaluate in a healthy population normal spectroscopic fat content (FC) values of the hip bone marrow and to assess the influence of age and sex on bone marrow conversion. Materials and Methods Eighty volunteers (40 men; 40 women; ages: 20–60 years; divided into four consecutive groups) underwent acetabulum, femoral head, femoral neck, greater trochanter, and diaphysis localized 1H MR spectroscopy. FC values of each anatomical site were obtained according to the following formula: Fat content = CH2/(CH2 + Water)*100. To assess bone marrow conversion, a spectroscopic conversion index (SCI) was calculated as FC neck/FC greater trochanter. Results FC values showed a gradient as follows: greater trochanter > femoral head > femoral neck > diaphysis > acetabulum in every age group both in men and in women. SCI increased with age both in men and women, showing lower values in women for every age group. Conclusion We obtained normal spectroscopic FC values from different areas of the hip, according to age and sex. These values may be used as reference values to evaluate, by the means of 1H MR spectroscopy, pathological conditions affecting hip bone marrow. J. Magn. Reson. Imaging 2014;39:369–376. © 2013 Wiley Periodicals, Inc.